Adequacy of Surgical Pathology Reporting of Breast Cancer in Different Hospitals - Fariba Abbasi; hushyar Azari; Arefeh Jafarzadeh (Journal of Research in Applied and Basic Medical Sciences, 2022)
Background & Aims: To determine how well the standard criteria were utilized in reporting breast cancer pathology and to compare the variability among a public teaching, a public nonteaching, and a private hospital in Urmia, Iran. Materials & Methods: Three hundred and fifty pathology reports of mastectomy samples with diagnosis of primary breast cancer were retrieved from archives of pathology departments of three hospitals; one public teaching (121 reports), one public nonteaching (99 reports), and one private hospital (130 reports). The reports were assessed for tumor laterality, size, color, consistency, type and grade, sample size, description of prior biopsy site, specimen condition (fresh, or in fixative), number of excised and involved lymph nodes, previous frozen section (FS), surgical margins, lymphovascular invasion, and in situ carcinoma. Results: None of the reports had all the suggested items. Specimen condition was the only item recorded in all of the reports. The teaching hospital reports had significantly higher number of reported items than the two other hospitals (P<0.001). Key items (tumor size, type and grade, surgical margin, vascular invasion, and in situ carcinoma) were also indicated more frequently in teaching hospital (P<0.001). Conclusion: We showed evident variations in reporting breast cancer pathology in the studied different hospitals. It seems that the teaching program in the public-teaching hospital can be a reason for the better results in this hospital. So we suggest using standard universal protocols for cancer reporting as well as creating an effective audit system to evaluate complete utilization of the protocols.